A Diverse Membrane Interaction Network for Plant Multivesicular Bodies: Roles in Proteins Vacuolar Delivery and Unconventional Secretion - Hu, Shuai; Li, Yan; Shen, Jinbo (Frontiers in Plant Science, 2020)
Vesicle trafficking between the membrane-bound organelles in plant cells plays crucial roles in the precise transportation of various materials, and thus supports cell proliferation and cellular polarization. Conventionally, plant prevacuolar compartments (PVCs), identified as multivesicular bodies (MVBs), play important roles in both the secretory pathway as intermediate compartments and the endocytic pathway as late endosomes. In recent years, the PVC/MVBs have been proposed to play important roles in both protein vacuolar delivery and unconventional secretion, but several important questions on the new regulators and environmental cues that coordinate the PVC/MVB–organelle membrane interactions and their biological significances remain. In this review, we first summarize the identity and nature of the plant PVC/MVBs, and then we present an update on our current understanding on the interaction of PVC/MVBs with other organelles in the plant endomembrane system with focus on the vacuole, autophagosome, and plasma membrane (PM) in plant development and stress responses. Finally, we raise some open questions and present future perspectives in the study of PVC/MVB–organelle interactions and associated biological functions.